2020
DOI: 10.1055/s-0040-1721066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Scribes on Efficiency in Academic Ophthalmology Practice

Abstract: Objective The aim of the study is to determine the effects of scribes on efficiency in an academic ophthalmology practice. Design This is a quality improvement study conducted by two ophthalmologists at an academic ophthalmology practice at UT Health San Antonio from January 2018 to April 2018. Implementation of scribes in practice was the primary intervention. Session time, patient encounter time, and template time adherence were recorded pre- and post-intervention. A second retrospective arm of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Our findings in the VA setting are consistent with previous non-VA studies that found associations between scribe intervention and increased productivity. 8 , 13 15 In our study, randomization to the scribe pilot was associated with improved productivity when measured as visits per FTE and RVUs per FTE, but not patients per day per provider, which may be a result of the lack of FTE adjustment in that measure. Although scribes’ assistance may increase providers’ availability in the clinic and reduce wait times, 22 , 33 , 34 providers’ scheduling patterns and administrative staff support are also key to reducing wait times.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Our findings in the VA setting are consistent with previous non-VA studies that found associations between scribe intervention and increased productivity. 8 , 13 15 In our study, randomization to the scribe pilot was associated with improved productivity when measured as visits per FTE and RVUs per FTE, but not patients per day per provider, which may be a result of the lack of FTE adjustment in that measure. Although scribes’ assistance may increase providers’ availability in the clinic and reduce wait times, 22 , 33 , 34 providers’ scheduling patterns and administrative staff support are also key to reducing wait times.…”
Section: Discussionmentioning
confidence: 59%
“…Evidence from past studies suggests that the use of medical scribes may be associated with increased productivity in a variety of clinical settings, although not uniformly. Studies found that scribes may be associated with increased provider productivity measured by the number of patients seen per hour or relative value units (RVUs) per hour in primary care, 8 12 specialty care, 13 16 and emergency department settings. 17 19 Only a few studies have examined the impact of scribes on provider satisfaction, time spent on documentation, time spent face-to-face with patients, and patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%